Thermal contraction crack polygons in Nunavik (northern Quebec): Distribution and development of polygonal patterned ground. (23rd May 2022) - Chiasson, Alexandre; Allard, Michel
Abstract: We evaluated the spatial distribution and morphological variability of thermal contraction crack polygon (TCCP) networks across Nunavik, a 440, 000‐km 2 region of northern Québec that spans the northward transition from discontinuous to continuous permafrost. A population of 4, 567 TCCP sites was sampled and analyzed from 80, 737 georeferenced high‐resolution aerial photographs and 264, 504 km 2 of ESRI satellite basemaps. For each site, six parameters were inventoried and compiled into a database: (a) network geometric arrangement; (b) intersection angles; (c) number of subdivisions and nested polygons (referred to as generations of development); (d) dominant polygon morphology; (e) surficial geology; and (f) vegetation cover. Statistical analyses of the tabulated data revealed a strong association between Holocene glacial, glacio‐fluvial, fluvial, marine, and organic landforms and the different intersections angles in the networks, providing insight into how the processes of thermal contraction cracking function and manifest geomorphically across varied permafrost landscapes. Orthogonal polygons (intersection angle of 90°) dominate on flat terrains where the thermo‐mechanical stresses are probably spatially homogeneous. Hexagonal (angles of 120°) and poorly structured polygons tend to form where topography variability probably generates heterogeneous heat flow patterns and thermo‐mechanical stresses in the ground, resulting in irregular cracking patterns.